Clean hands, safe care: how knowledge, attitude, and practice impact hand hygiene among nurses in Najran, Saudi Arabia - Al-Qahtani, Awad Mohammed (Frontiers in Public Health, 2023)
Aim This study aimed to assess nurses' knowledge and attitudes towards hand hygiene guidelines in Najran city, determine compliance levels, identify factors contributing to non-compliance, and provide recommendations for interventions to improve hand hygiene practices and reduce healthcare-associated infections risk. Subject and methods This cross-sectional study was conducted among nurses working in the selected government hospitals in Najran City, Saudi Arabia. A self-administered questionnaire was distributed among the targeted nurses using an online survey. The questionnaire includes socio-demographic characteristics such as age, gender, and marital status. The questionnaire had 25 items to measure knowledge, 10 to measure attitude, 6 to measure practices, and 4 to measure the impact of COVID-19 on hand hygiene practices. Results Among the 386 nurses recruited, 88.3% were females, and 25.6% were aged between 31 to 35 years old. Overall, good knowledge, positive attitude, and good practice levels were found in 42.5%, 48.4%, and 94%, respectively. The common factor influencing hand hygiene practice was the prevention of cross-infection (88.1%). The total knowledge score mean was 18±3.4 (highest possible score: 25). The total attitude score mean was 37.5 ± 6.1 (highest possible score: 50). The total practice score mean was 26.9 ± 2.8 (highest possible score: 30). A higher score indicates higher KAP of hand hygiene. Factors associated with increased KAP were being older in age (Z=6.446; p<0.001), gender female (Z=9.869; p<0.001), being a Filipino nurse (H=117.8; p<0.001), working in a surgery department (H=28.37; p<0.001), having more than ten years of experience (Z=6.903; p<0.001), living in shared accommodation (H=87.22; p<0.001), having associated chronic disease (Z=4.495; p<0.001), and receiving formal training in hand hygiene (Z=2.381; p=0.017). There was a positive highly statistically significant correlation between knowledge score and attitude score (r=0.556), between knowledge score and practices score (r=0.303), and between attitude score and practices score (r=0.481). Conclusion The nurses' knowledge, attitude, and practice in regards to hand hygiene were deemed acceptable. We noticed that female nurses who were older and had more experience, as well as those who had received formal hand hygiene training, displayed better KAP compared to their counterparts.